1978
DOI: 10.1002/cpt1978242192
|View full text |Cite
|
Sign up to set email alerts
|

Dose response to chlorthalidone in patients with mild hypertension; Efficacy of a lower dose

Abstract: A multicenter study of chlorthalidone was performed to determine the relative antihypertensive efficacy and side effects of doses lower than those usually recommended for therapy. After a 4-wk placebo control period 100 patients with mild hypertension were randomly assigned doubleblind to 12.5-, 25-, 50-, or 75-mg regimens of chlorthalidone or to placebo for 12 wk. The groups of patients taking 25, 50, and 75 mg had declines in blood pressure which were not significantly different from each other. Serum potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(27 citation statements)
references
References 1 publication
0
25
1
1
Order By: Relevance
“…This dissociation between the diuretic dose-response curves for blood pressure reduction and those for serum potassium and uric acid levels, for example, is now well known. 25 In this study, however, there were no observed differences in subjective side effects between the two dose groups.…”
Section: -21contrasting
confidence: 56%
“…This dissociation between the diuretic dose-response curves for blood pressure reduction and those for serum potassium and uric acid levels, for example, is now well known. 25 In this study, however, there were no observed differences in subjective side effects between the two dose groups.…”
Section: -21contrasting
confidence: 56%
“…Diuretic-related reductions in serum K ϩ are typically dose related and usually range from 0.2 to 0.6 mmol/L. [11][12][13][14][37][38][39][40][41] This well-described relationship is depicted by arrow "A" in Figure 1. A recent meta-analysis of 59 studies involving 83 thiazide diuretic treatment arms found a significant correlation between the degree of diuretic-induced hypokalemia and the increase in plasma glucose, and there was evidence that prevention of hypokalemia with K ϩ supplementation or potassium-sparing agents lessened the degree to which plasma glucose increased consequent to diuretic therapy.…”
Section: Possible Relationship To Hypokalemiamentioning
confidence: 99%
“…Data obtained with chlorthalidone so far indicate that the plateau of the dose-response antihypertensive curve is reached with a daily dose of 25 mg and that increasing the dosage does not increase the BP-lowering effect but further increases the occurrence of negative metabolic effects, principally hypokalemia (10,11). Data obtained with hydrochlorothiazide, the most widely used thiazide diuretic in clinical practice, are less certain and suggest that the plateau of the dose-response BP-lowering curve is reached with the dose of 50 mg/d, whereas negative metabolic effects, principally hypokalemia, occur in a dosedependent manner with a dose up to 100 mg/d (9,12).…”
Section: Choice Of Optimal Dosementioning
confidence: 99%